PERSEPSI PARA HAKIM PENGADILAN AGAMA KABUPATEN MALANG TERHADAP KEDUDUKAN HUKUM ANAK DI LUAR NIKAH : Sebelum dan Setelah Putusan Mahkamah Konstitusi Nomor 46/PUU/VII/2010 - Ahmad Muhtar Syarofi; Bahrul Ulum (Jurnal Penelitian Ilmiah INTAJ, 2020)
Status of children out of wedlock in Indonesia, which is currently associated with many (having a civil relationship) other than with mother but also with her father. Problems in this article, namely: Constitutional Court Decision Number 46 / PUU / VII / 2010 and, how the rights and obligations of children outside of Marriage before and after the Decision of the Constitutional Court Number 46 / PUU-VIII / 2010. Because in the Malang District Religious Court there are many civil cases as described in the Case statistics. The method of approach used in this study is the research of qualitative description and legal sociology (legal research, rechtsonderzoek) and libre researce. Qualitatively analyzed, namely from primary data from interviews and secondary theories. The results of the study show that the perceptions of the judges of Malang Regency religious court in the case of children out of wedlock can get their rights by considering aspects of justice and the child's needs.